Salidroside promotes pro-angiogenesis and repair of blood brain barrier via Notch/ITGB1 signal path in CSVD Model - Tu Zhilan; Zhang Zengyu; Jin Pengpeng; Yang Hualan; Li Chao; Xi Yan; Guo Zimin; Hou Shuangxing; Li Weiwei (Journal of Advanced Research)
Introduction: Salidroside (SAL), extracted from Rhodiola rosea, has been widely used in coronary heart disease and myocardial ischemia for decades. Previous studies have demonstrated that SAL could reduce arteriosclerosis, and thus combat ischemic brain damage. However, the in-depth function of the salidroside in Cerebral Small Vascular Disease (CSVD) has not been discovered, and related molecular mechanism is still unclear. Objectives: The present study aims to explore the effects of salidroside in angiogenesis as well as repair of blood brain barrier (BBB) and its possible mechanisms. Methods: We established a rat model of SHR via 2-vessel gradual occlusion (SHR-2VGO) to mimic the CSVD. Subsequently, the MRI, pathomorphism, as well as Morriss water maze test were conducted to determine CSVD-related indicators. 8 weeks post-surgery, animals were randomly administered SAL, DAPT, ATN161 or saline.The aim was to explore the protective effects of SAL in CSVD as well as its possible mechanism. Results: Here we found that SAL could attenuate cerebral hypoperfusion-induced BBB disruption, promote the pro-angiogenesis through enhancing the cell budding. Further investigations demonstrated that SAL could significantly increase the expression of Notch1, Hes1, Hes5, and ITGB1. In addition, we confirmed that SAL could activate Notch signal path, and then up-regulate ITGB1 to promote pro-angiogenesis and thus protect BBB from disruption. Conclusion: The aforementioned findings demonstrated that SAL could protect BBB integrity through Notch-ITGB1 signaling path in CSVD, which indicated that SAL could be a potential medicine candidate for CSVD treatment.